UPAYA PENINGKATAN KINERJA PEDAGANG KAKI LIMA DI KOTA SURAKARTA MELALUI ORIENTASI KEWIRAUSAHAAN DAN KOMPETENSI KEWIRAHAAN - Hariyanti Hariyanti; Nuryati Nuryati (ProBank, 2019)
This research is  to  analyze the  effect of  entrepreneurial orientation on performance through entrepreneurial competence at street vendors in the city of Surakarta. A sample of 99 street vendors. The analytical tool used is path analysis. The results of the study show that (1). Equation model 2 is the best model to explain performance through entrepreneurial orientation and entrepreneurial competence, (2) entrepreneurial orientation as measured by innovation, proactivity, risk-taking and entrepreneurial competence has a positive and significant effect on performance.the results of  this study can  be  expected to  contribute to police studies for the  development to entrepreneurial orientation and entrepreneurial competence of street vendors, especially street vendors who sellin the of Surakarta.